Optimalisasi Peran Baitul Maal Wa Tamwil (BMT) dalam Pemberdayaan Umkm: Pendekatan Maqashid Syariah dan Inklusi Keuangan - Neng Ulpa Apipah; Ani Indah Sari; Sri Rokhlinasari; Alvien Septian Haerisma (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
This study investigates the role of Baitul Maal wa Tamwil (BMT) in empowering Micro, Small, and Medium Enterprises (MSMEs) through the integration of Maqashid Sharia principles and financial inclusion strategies. Despite the strategic importance of MSMEs in economic growth and poverty reduction, many face challenges in accessing formal financial services. BMT, with its dual function of social (maal) and commercial (tamwil) activities, offers a unique platform to bridge this gap. Using a qualitative systematic literature review guided by PRISMA, this study analyzes 30 relevant articles to examine BMT operational models, implementation of Maqashid Sharia objectives, financial inclusion practices, and their impact on MSME performance. Findings indicate that BMT effectively supports MSMEs in capital access, income generation, and business resilience, but inconsistencies in balancing social and commercial objectives limit. holistic empowerment. Integrating Maqashid Sharia principles enhances ethical and sustainable outcomes, while financial inclusion expands outreach to underserved entrepreneurs. Optimization strategies, including strengthening institutional capacity, combining financial and non-financial support, and context-specific interventions, are essential for maximizing BMT effectiveness. This study contributes a comprehensive framework linking ethical, financial, and empowerment dimensions, offering practical guidance for policymakers and BMT managers in promoting inclusive and sustainable MSME development.